RUMAH SAKIT UMUM SWASTA KELAS C DENGAN FASILITAS TAMAN TERAPI DI KABUPATEN WONOGIRI - Tambunan, Jean Elisabet; Farkhan, Ahmad; Yuliani, Sri (ARSITEKTURA, 2016)
Designing Private General Hospital Class C in the Kabupaten Wonogiri motivated by needs of society to have better health services, the increased of population growth was offset by increasing the number of health facilities, the spread of hospital in Wonogiri is unequal, Kabupaten Wonogiri is lack of 283 beds, the rumors about reduction of hospitals grade with facilities of Badan Penyelenggara Jaminan Sosial. The purpose of this design is to generate design of hospital buildings as a place for people of Wonogiri and communities outside Wonogiri, to obtain health facilities as the main reference with the capability of service that are adjusted to the regulation standard of Class C Hospital by using a healing garden as a healing facility or therapy. So far, the existing paradigm regarding hospital is the patients often feel uncomfortable when receiving medical and treatment due to the circumstances of the hospital which is seemed creepy and claustrophobic for patients. So it can trigger stress of them which can cause patient's immune system becomes depressed so that the process of recovery and healing the patient became obstructed. The method used is a method of designing the architecture, applied to the hospital building with characteristics of physical environment of a hospital facility must be designed by emphasizing the comfortability and safety for patients, with healing garden facilities aims to reduce stress levels of patients who will be treated at the hospital.